Pelatihan Parenting untuk Meningkatkan Komunikasi Interpersonal Siswa SMP di Kecamatan Pulogadung Jakarta Timur - Happy Karlina Marjo; Wirda Hanim; Awaluddin Tjalla (Universitas Mathla'ul Anwar Banten, 2021)
PARENTING TRAINING TO IMPROVE INTERPERSONAL COMMUNICATION OF JUNIOR HIGH SCHOOL STUDENTS IN PULOGADUNG DISTRICT, EAST JAKARTA. To improve the quality of community empowerment and efforts to achieve educational goals, community service entitled “Parenting Training to Improve Interpersonal Communication for Students of SMP YWKA II Rawamangun in Pulogadung District, East Jakarta”.This community service is carried out with the following targeted results in the first year in the form of parenting training results with studies of related disciplines and theories to form awareness and understanding of parents in improving communicative interpersonal communication patterns between parents and students of SMP YWKA II Rawamangun in Pulogadung sub-district, East Jakarta.The results of parenting training showed that from 7 parents of students, the results were: 6 parents of students in the medium to high category of interpersonal communication skills, meaning that there was an increase in interpersonal communication skills by 85.71% from the fairly good category, increasing to very good. . Meanwhile, 1 student's parents both pre-test and post-test results were fixed, meaning that 14.29% there was no increase in the very good category. Community service, especially parents of students, with a limited test on parenting training to improve interpersonal communication skills between parents and children/students at SMP YWKA Rawamangun shows that the increase in knowledge, attitudes and interpersonal communication skills is very good.